INTERNAL AND EXTERNAL FACTOR ON NON-PERFORMING LOANS AND ITS IMPLICATIONS TOWARDS PROFITABILITY - Aditya Sovana; Tb. Hasanuddin; Ellen Rusliati (Faculty of Economic and Business, University of Pasundan, 2021)
Non-performing loans will effect to the bank losses due to non-receipt of the funds that have been distributed along with the interest income. This research aims to find out and analyze the impact of internal and external factors on non-performing loans distributed to the Small and Medium-sized Enterprises and its implications towards profitability of Bank BJB. The method used in this research is descriptive and verifiative, while data collection was carried out through interview, observation, and documentation. The sample was also collected by purposive sampling, by analyzing and using path analysis. The result showed that the internal and external factor did give impact to the non-performing loans, both simultaneously and partially. The loans also gave impact to the profitability of Bank BJB.